Transforming the lifestyle of modern athletes: The impact of wearable and E-sports technologies on physical and mental health in a sustainable event ecosystem - Kuncoro, Moh. Ali; Nurhasan, Nurhasan; Kartiko, Dwi Cahyo; Turi, Moh; Kristiyandaru, Advendi (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the impact of technology, especially wearables, the application of sustainability in sports events, and involvement in e-sports on the physical performance, mental health, and physical performance of individuals in the field of sports. The methods used are quasi-experiments and surveys. The population consists of athletes, sports event organizers, and e-sports gamers. A total of 100 athletes (50 experimental groups and 50 controls) participated in an experiment using wearable technology. In addition, 150 sports event organizers and 150 e-sports gamers participated in the survey. Results showed that the use of wearable technology significantly improved athletes' physical performance (p = 0.000) and lowered stress levels (p = 0.006). The application of sustainability strategies in sports events has been proven to improve energy efficiency (p = 0.000) and reduce waste (p = 0.002). Meanwhile, active involvement in e-sports contributed to an improvement in gamers' mental health (p = 0.004), but negatively impacted their physical health (p = 0.005). In conclusion, wearable technology and sustainability strategies contribute positively to the performance and sustainable future of sports.